Effects of Digital Filtering in Data Processing of Seismic Acceleration Records. (23rd January 2007) - Mollova Mollova, Guergana Guergana
Abstract : The paper presents an application of digital filtering in data processing of acceleration records from earthquakes. Butterworth, Chebyshev, and Bessel filters with different orders are considered to eliminate the frequency noise. A dataset under investigation includes accelerograms from three stations, located in Turkey (Dinar, Izmit, Kusadasi), all working with an analogue type of seismograph SMA-1. Records from near-source stations to the earthquakes (i.e., with a distance to the epicenter less than 20 km) with different moment magnitudesMw = 3.8, 6.4, and 7.4 have been examined. We have evaluated the influence of the type of digital filter on time series (acceleration, velocity, displacement), on some strong motion parameters (PGA, PGV, PGD, etc.), and on the FAS (Fourier amplitude spectrum) of acceleration. Several5 % -damped displacement response spectra applying examined filtering techniques with different filter orders have been shown. SeismoSignal software tool has been used during the examples.